Centella asiatica and its carbonaceous composites as novel materials for photocatalytic and electrochemical applications. (2021) - Vinutha, K.; Divakara, M.B.; Veena, K.; Anil Kumar, M.R.; Ravikumar, C.R.; Santosh, M.S.; Nagaswarupa, H.P.; Avinash, B.; Gurushantha, K.
Abstract: In the recent times, global interest on plant-based research has increased significantly. Through this article, a simple heat treatment method to synthesize Centella asiatica (CA) powder has been suggested. The synthesized samples have been subjected to various structural and morphological characterizations, in addition to electrochemical studies. Although the medicinal value of Centella asiatica is well known, its use in other applications is hardly explored. Hence, by combining the cyclic nature of CA and the layered structures of carbonaceous materials, composites of Centella asiatica with graphite powder, GO and rGO have been prepared for the first time and their photocatalytic and electrochemical properties have been investigated. In spite of some agglomeration and flake like structures, the nanosize (14 nm) of the prepared CA sample contributes largely to the aforementioned applications. One of the phenomenal aspects of the synthesized sample is that the low energy gap and high conductivity makes it an excellent photocatalytic material which is also evident from its ability to decolorize AO 8 dye under UV light to a great extent. Among the composites of CA-carbonaceous materials prepared, Centella asiatica-rGO exhibited superior electrochemical properties with high capacitance and low charge transfer resistance.